Branched short elastin‐like peptides with temperature responsiveness obtained by EDTA‐mediated multimerization. (9th September 2022) - Tanaka, Naoki; Suyama, Keitaro; Tomohara, Keisuke; Maeda, Iori; Nose, Takeru
Abstract : Elastin‐like peptides (ELPs) exhibit a reversible phase transition, known as coacervation, triggered by temperature changes. This property makes them useful as stimuli‐responsive molecular materials for various applications. Among ELPs, short peptide chain lengths have some advantages over long peptide chain lengths because short ELPs can be easily obtained by chemical synthesis, allowing the use of various amino acids, including D‐type and unnatural amino acids, at any position in the sequence. Moreover, the incorporated amino acids readily affect the temperature‐responsive behavior of ELPs. However, to be utilized in various applications, it is necessary to develop short ELPs and to investigate their temperature‐responsive properties. To obtain further insights into the temperature‐responsive behavior of the short ELPs, we investigated branched short ELP analogs composed of (FPGVG)n chains ( n  = 1 or 2, abbreviated as F1 and F2, respectively). We synthesized multimers composed of four F1 chains or two to four F2 chains using ethylenediaminetetraacetic acid (EDTA) as a central component of multimerization. Our results show that the multimers obtained exhibited coacervation in aqueous solutions whereas linear F1 or F2 did not. Furthermore, the structural features of the obtained multimers were the same as those of linear (FPGVG)4 . In this study, we demonstrated that molecules capable of coacervation can be obtained by multimerization of F1 or F2. The temperature‐responsive molecules obtained using short ELPs make it possible to use them as easy‐to‐synthesize peptide tags to confer temperature responsiveness to various molecules, which will aid the development of temperature‐responsive biomaterials with a wide variety of functions. Abstract : Branched elastin‐like peptide (ELP) analogs were synthesized using ethylenediaminetetraacetic acid and short (FPGVG)n chains ( n  = 1 or 2). Unlike the linear FPGVG or (FPGVG)2, the multimers composed of four FPGVG chains or two to four (FPGVG)2 chains exhibited coacervation. The multimerization of FPGVG or (FPGVG)2 units is an effective approach to obtain molecules exhibiting reversible self‐assembly corresponding to temperature changes.